MCSE Windows 2000 network infrastructure administration : - Robichaux, Paul E. (Sybex, 2001)
This book is an excellent adjunct for any serious test taker; Microsoft's wise move of adding MCSE sample questions has made the decision to buy this book a lot easier. It also has some classic sections on addressing and name resolution. But for most students this book will be read in addition to other books; it won't be a primary source. --William Steinmetz